Aureobasidium pullulans culture supernatant significantly stimulates R-848-activated phagocytosis of PMA-induced THP-1 macrophages. (August 2013) - Tamegai, Hidekazu; Takada, Yuka; Okabe, Mitsuyasu; Asada, Yukoh; Kusano, Kisato; Katagiri, Yohko U.; Nagahara, Yukitoshi
Abstract Toll-like receptors (TLRs), which recognize a wide range of microbial pathogens and pathogen-related products, play important roles in innate immunology. Macrophages have a variety of TLRs, and pathogen binding to TLR resulted in the activation of macrophages. R-848, an immune response modifier, is an analog of imidazoquinoline derivative and binds to an endosome-localized TLR to exert an anti-viral response on leukocytes. In the present study, we verified that co-treatment of R-848 with other TLR agonists would enhance immune response. The culture supernatant of Aureobasidium pullulans (A. pullulans, which contains predominantly soluble β-glucan), which binds to cell membrane-localized TLR, and to C-type lectin receptor Dectin-1, was treated together with R-848 to THP-1 macrophages. Compared to R-848 treatment alone, co-treatment of R-848 with A. pullulans culture supernatant significantly augmented TNF-α and IL-12p40 cytokine expression. Next, we investigated whether or not apoptotic cell uptake would be increased by co-treatment of R-848 with A. pullulans culture supernatant. To detect engulfed apoptotic cells, we induced apoptosis in human lymphoma Jurkat cells by 5-fluorouracil and stained them with fluorescent dye 5(6)-carboxytetramethylrhodamine (TAMRA), whereas THP-1 macrophage was labeled with fluorescein isothiocyanate-anti-CD14 and determined the percentage increase in TAMRA-positive THP-1 macrophages by flow cytometric assay. Since R-848 or A. pullulans treatment alone stimulated THP-1 macrophages to induce phagocytosis, co-treatment of R-848 with A. pullulans culture supernatant significantly augmented phagocytosis of apoptotic Jurkat cells. These results suggest that the activation of several different innate immune receptor pathways may enhance the immune response of R-848 significantly.